2017
DOI: 10.1590/0034-737x201764010006
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting the implementation of mechanical harvesting of sugarcane in Campos dos Goytacazes, RJ, Brazil

Abstract: RESUMOThe objective of this research was to identify and characterize the main technical factors that affect the deployment of the mechanized harvesting of sugarcane in Campos dos Goytacazes, Rio de Janeiro, Brazil. In general, it can be stated there were restrictive factors related to machinery, administrative management, and technical planning. We identified significant technical restrictions in the planting system, particularly in relation to the size and shape of the plots, length of the rows, row spacing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…index (Solano et al, 2017). It can also assist in the calculation of outsourcing contracts for mechanized sugarcane cutting operations in processing plants, since supporting parameters for defining these contracts are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…index (Solano et al, 2017). It can also assist in the calculation of outsourcing contracts for mechanized sugarcane cutting operations in processing plants, since supporting parameters for defining these contracts are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Recommendations presented in the literature which were reviewed in this paper (Benedini and Conde, 2008;Bharati et al, 2017;Paixão et al, 2016;Solano et al, 2017) included the objective function (1) which aimed to minimize the number of harvest machine maneuvers in the plot j and, simultaneously, take advantage of the plantation area with constraints on the dimensions and area of the plots. Constraint (2) imposed boundaries, lower (Area low ) and upper (Area upp ), on the areas of the plots.…”
Section: Plot Generation Problemmentioning
confidence: 99%
“…This protocol established the complete elimination of the practice of sugarcane burning in 2017 (Cervi et al, 2015). Solano et al (2017) identified the main technical factors that affect the implementation of mechanized harvesting systems. The authors identified important technical constraints in the system of planting, particularly the size and shape of the plots, the appropriate row spacing and the selection of sugarcane varieties suitable for mechanical harvesting.…”
Section: Introductionmentioning
confidence: 99%